Emancipation through Deliberation? Some Reflections about the First Records of the Communal Council of Trets (Provence, 1340) (Edad Media. Revista de Historia, 2020)
By looking into a hitherto unpublished brief record of communal deliberations, this article explores the modalities of political action employed by a community of average importance which turn it into the political partner of the seigniorial authority and provide it with the rhetorical and juridical tools necessary for its collective construction. The analysis of the record using the method provided by the so-called ‘Archaeology of the Written’ reveals the precise moment (July 1340) when the Council of Trets invests itself with authority by giving its deliberations an executive force. This is the outcome of a slow process of political maturing which began in 1320, one which sees the progressive unification of a community divided by the effects of co-seigneury and its vindication of its old liberties in the face of the seigniorial claims and the county fiscal demands.
Keywords: Provence; Universitas; Town Council; Deliberation; Laws; Common Good; Seigneury